Erratic migration of Ascaridia hermaphrodita (Nematoda: Ascaridida) in a blue-fronted Amazon parrot (Amazona aestiva) from illegal wildlife trade: case report - R.S. Siqueira; R.B. Lucena; R.R. Guerra; V.L.R. Vilela; R.H. Vasconcelos; A.M.G.G. Quaresma; F. Riet-Correa (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2021)
ABSTRACT Ascaridiasis by Ascaridia hermaphrodita is a common parasitic disease in blue-fronted Amazon parrots (Amazona aestiva) and the contamination occurs by ingestion of eggs. Illegal trade of wild birds can increase the frequency of visceral erratic migration by this parasite. Hence, this report describes the erratic migration of A. hermaphrodita and associated lesions in a blue-fronted Amazon parrot. This is a retrospective study, which originated from several apprehension of illegal birds in the state of Paraíba, Brazil. Necropsy revealed intense intestinal ascarid infestation. Hepatic lesions were also observed associated with the parasite migration. Stereoscopy allowed the identification of the morphology of the parasites. Summarizing, this condition in wild birds is not fully understood and may be associated with illegal trade.